The Influence of Regional Expenditure on The Regional Economy in Regencies and Cities in Indonesia - Prayoga, Ronaldy; Pratama, Kristian Abillio (Universitas Batanghari Jambi, 2025)
This study aims to see how the contribution of personnel, goods and services, and capital expenditures, the component of expenditure with the most significant portion of local government, influences the regional economy (GRDP). The data used in this study are data on the realization of personnel expenditure, goods and services expenditure, capital expenditure, and GRDP data to represent the regency and city regional economy from 2010 to 2019. The sample in this study is all regencies and cities in Indonesia that meet the criteria, namely 480 regencies and cities. Data is taken from the websites of the Central Agency of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK). The results showed that personnel, goods and services, and capital expenditures both partially and simultaneously positively and statistically significantly affected the regional economy (GRDP).